Religion, secularism, and political belonging - Medovoi, Leerom; Bentley, Elizabeth (Duke University Press, 2021)
The contributors to Religion, Secularism, and Political Belonging examine how the new political worlds that are emerging--from Trump's America to the post-Arab-Spring Middle East--intersect with locally specific articulations of religion and secularism.